Images of the woman reader in Victorian British and American fiction - Golden, Catherine (University Press of Florida, 2003)
"By comparing 'ideologies surrounding women and books' on both sides of the Atlantic, it offers new interpretations of canonical texts in a series of fascinating pairings of British and American texts. ... The most original aspect of the book is its examination of the woman reader as she appeared in illustrations in popular novels and the way illustration functioned as a vehicle for illuminating issues of gender.